2005
DOI: 10.1002/pmic.200400943
|View full text |Cite
|
Sign up to set email alerts
|

The membrane proteome of Halobacterium salinarum

Abstract: The identification of 114 integral membrane proteins from Halobacterium salinarum was achieved using liquid chromatography/tandem mass spectrometric (LC/MS/MS) techniques, representing 20% of the predicted alpha-helical transmembrane proteins of the genome. For this experiment, a membrane preparation with only minor contamination by soluble proteins was prepared. From this membrane preparation a number of peripheral membrane proteins were identified by the classical two dimensional gel electrophoresis (2-DE) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
94
0
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(104 citation statements)
references
References 57 publications
8
94
0
2
Order By: Relevance
“…salinarum have been reported (e.g. Karadzic & Maupin-Furlow, 2005;Klein et al, 2005;Tebbe et al, 2005). It was shown that proteome analysis can also be used to improve genome annotation in halophiles.…”
Section: Genetics and Functional Genomicsmentioning
confidence: 99%
“…salinarum have been reported (e.g. Karadzic & Maupin-Furlow, 2005;Klein et al, 2005;Tebbe et al, 2005). It was shown that proteome analysis can also be used to improve genome annotation in halophiles.…”
Section: Genetics and Functional Genomicsmentioning
confidence: 99%
“…NRC-1 (2,17,34,35). A total of 972 (P Ͼ 0.9) unique proteins have been identified in this and our previous (17) proteome analyses.…”
Section: Figmentioning
confidence: 52%
“…Using a ProteinProphet probability of 0.9 as the cutoff, most of the proteins (89 of 162 membrane, 218 of 226 soluble, and 26 of 29 membrane/soluble fraction proteins) found in our previous analysis were also identified in this study. The proteome analysis of a closely related strain, H. salinarium, resulted in the identification of 802 proteins in the soluble proteome (34) and 141 proteins in purified membrane (35). The H. salinarium proteome analyses detected ϳ680 unique proteins classified as reliable or trusted identifications.…”
Section: Figmentioning
confidence: 99%
“…The flow-through was collected. A step-wise elution was performed using 20 μL of 30% acetonitrile in different concentrations of NH4FA (20,30,40,50, 60 and 120 mM, pH 3). All fractions were dried in vacuo and resuspended in 5% formic acid to allow analysis by nanoLC-MS/MS.…”
Section: Separation Of Peptides By Strong Cation Exchange Chromatographymentioning
confidence: 99%
“…enterica (previous S. typhimurium) (28), 14 from Klebsiella pneumoniae (27), and 15 from green-sulfur bacterium Chlorobium tepidum (1). Using sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) in combination with liquid chromatography-tandem mass spectrometry (LC-MS/MS), 114 integral membrane proteins were identified in Halobacterium salinarum (20) and 79 membrane proteins were detected in Mycobacterium tuberculosis (14). Emerging gelfree proteomic approaches have provided powerful tools for the analysis of complex mixtures and have made membrane proteins accessible for mass spectrometric proteomic analysis (43).…”
mentioning
confidence: 99%